Mental health practices in the family health strategy: a bibliographic study - Álissan Karine Lima Martins; Violante Augusta Batista Braga; Ângela Maria Alves e Souza (Rev Rene)
This is a bibliographic study which aims to analyze Brazilian researches which focus on mental health in the context of the Family Health Strategy (FHS) facing the current health policy and mental health as well as the principles of psychiatric reform. The inquiry was made by searching the BIREME data basis using the keywords “Mental Health” and “Family Health Program”. The publications consisted of articles provided with an index accessible in full, collected in May, 2008. The analysis was made through exploratory, selective, analytical and hermeneutic reading. Even considering the psychiatric reform process in the country as well as the recent experiences with mental health action inclusion in the Family Health Strategy, a restrict number of publications is pointed out. The publications show limitations to the mental health approach in the FHS, concerning high demand, little practice with the thematic and priorization of actions in other areas.